The toxicity of heavy metals and plant signaling facilitated by biochar application: Implications for stress mitigation and crop production. (December 2022) - Khan, Zaid; Fan, Xianting; Khan, Mohammad Nauman; Khan, Muhammad Ayoub; Zhang, Kangkang; Fu, Youqiang; Shen, Hong
Abstract: Heavy metals (HMs) accumulation in soil poses a severe threat worldwide for soil, plants, and humans. The accumulation of HMs in soil and uptake by plants leads to disrupt physiological and biochemical metabolisms. As a potential and sustainable soil amendment, biochar has attained huge attention to reduce HMs toxicity in soil and improve plant growth influenced by HMs stress. Despite an array of research studies, there is a lack of knowledge on how biochar interacts with HMs, moderate plant defence system, induce HMs stress signals pathways and promote plant growth. At first, the review highlights the possible effects of HMs on soil and plant and their consequences on plant signaling network. Secondly, the biochar's impact on soil physiochemical properties and the sorption of HMs on biochar surface through direct and indirect mechanisms are reviewed. Finally, the review shows the key roles of biochar in soil improvement to enhance plant growth and signaling response to HMs by enhancing the activities of antioxidants and reducing chlorophyll injury, reactive oxygen species (ROS) accumulation, and cell membrane degradation under HMs stress. However, future studies are needed to evaluate the role of biochar in diverse climatic conditions as well as the long-term effects of biochar on HMs persistency in soil and crop productivity. This review will provide new avenues for future studies to address and quantify the advancement in biochar's role in alleviating plant's HMs stress on a sustainable basis. Graphical abstract: Graphical abstract Image 1 Highlights: Heavy metals (HMs) accumulation decline soil fertility and environment sustainability. Biochar is being recognized by scientists for its potential role, mitigating HMs toxicity and improving plant growth. Amendment of biochar modify physio-chemical and biological properties of soil. Biochar increase HMs sorption in polluted soils and promote plant signaling against HMs stress.